Structural and temporal dynamics analysis on drug-eluting stents: History, research hotspots and emerging trends - Lili Tan; Xiangxiu Wang; Kungshan Yuan; Tieying Yin; Ruolin Du; Li Shen; Zhirong Zhu; Suhua Yu; Haijun Zhang; Guixue Wang (Bioactive Materials, 2023)
Purpose: This review aims to explore the history, research hotspots, and emerging trends of drug-eluting stents(DES)in the last two decades from the perspective of structural and temporal dynamics. Methods: Publications on DES were retrieved from WoSCC. The bibliometric tools including CiteSpace and HistCite were used to identify the historical features, the evolution of active topics, and emerging trends on the DES field. Results: In the last 20 years, the field of DES is still in the hot phase and there is a wide range of extensive scientific collaborations. In addition, active topics emerge in different periods, as evidenced by a total of 41 disciplines, 511 keywords, and 1377 papers with citation bursts. Keyword clustering anchored five emerging research subfields, namely #0 dual antiplatelet therapy, #3 drug-coated balloon, #4 bifurcation, 5# rotational atherectomy, and 6# quantitative flow ratio. The keyword alluvial map shows that the most persistent research concepts in this field are thrombosis, restenosis, etc., and the emerging keywords are paclitaxel eluting balloon, coated balloon, drug-eluting balloon, etc. There are 7 recent research subfields anchored by reference clustering, namely #2 dual antiplatelet therapy, #4 drug-coated balloon, #5 peripheral artery disease, #8 fractional flow reserve, #10 bioresorbable vascular scaffold, # 13 intravascular ultrasound, #14 biodegradable polymer. Conclusion: The findings based on the bibliometric studies provide the current status and trends in DES research and may help researchers to identify hot topics and explore new research directions in this field.